Young Audience's Reception To Mars Romusha's Song "Barisan Pekerja" (1943) - Prajabnasti, Rosi Risalah (Jurnal Komunikasi, 2024)
Japanese occupation in Indonesia, even though it was relatively short, gave a painful memory and left historical traces for Indonesian people nowdays. One of the historical trace of Japanese occupation in Indonesia that can be accesses again is song of romusha march "Barisan Pekerja" (1943). This research explores how today's young audiences reads the song of Romusha march "Barisan Pekerja" (1943) as uploaded on YouTube and its relevance to today's conditions. This research is a qualitative study that uses Stuart Hall's encoding-decoding theory and elaborated with the theory of political memory to see the meaning of that song from young audiences. From 8 informants, 3 people have an oppositional position, 4 people have a negotiated position and 1 person has a dominant-hegemonic position. The acceptance of each informant is inseparable from factors such as the framework of knowledge and ideology possessed, identity background, work and experience and access informans to the song. In addition, the collective memory they have - about the past, present and future - is also formed from education and the environment around the informant which contributes to the acceptance of young audiences.